High School Drop-Outs: Characteristics of their Post School Learning - McCatty, Cressy A. M.; Virgin, Albert E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to investigate the extent and some of the characteristics of learning by high school drop-outs. Subjects were 70 men and 71 women who were resident in the Borough of North York and who had left secondary schools without graduating. An intensive, highly structured interview was used to collect the data. Findings support the view that drop-outs engage extensively in learning. The majority of the learning was planned by the learner himself; only 11% of the learning projects were carried out in a group setting. Nearly one-quarter of the learning projects were job related.